The Opposite House : Poems - Emerson, Claudia, 1957-2014 (Book collections on Project MUSE., 2015)
With graceful lines swooping like a bird in flight, Claudia Emerson's newest collection explores the harsh realities of aging and the limitations of the human body, as well as the loneliness, fear, and anger that can accompany us as we live. Keenly observed and beautifully executed, these poems move from the grim facade that hides beauty-prosthetic eyes- to the beautiful scene that conceals violence-a rural retreat. Emerson also considers once common things that are fast becoming obsolete: cursive writing, telephone booths, barbers. At once hopeful and cognizant of all the reasons why humans might despair, these poems echo with remarkable insight into the true nature of life.